The role of hypoxia in glioblastoma invasion - Monteiro, Ana (2017)
Glioblastoma multiforme (GBM), a grade IV astrocytoma, is the most common and deadly type of primary malignant brain tumor, with a patient's median survival rate ranging from 15 to 17 months. The current treatment for GBM involves tumor resection surgery based on MRI image analysis, followed by radiotherapy and treatment with temozolomide. However, the gradual development of tumor resistance to temozolomide is frequent in GBM patients leading to subsequent tumor regrowth/relapse. For this reason, the development of more effective therapeutic approaches for GBM is of critical importance. Low tumor oxygenation, also known as hypoxia, constitutes a major concern for GBM patients, since it promotes cancer cell spreading (invasion) into the healthy brain tissue in order to evade this adverse microenvironment. Tumor invasion not only constitutes a major obstacle to surgery, radiotherapy, and chemotherapy, but it is also the main cause of death in GBM patients. Understanding how hypoxia triggers the GBM cells to become invasive is paramount to developing novel and more effective therapies against this devastating disease. In this review, we will present a comprehensive examination of the available literature focused on investigating how GBM hypoxia triggers an invasive cancer cell phenotype and the role of these invasive proteins in GBM progression.